Screening and Optimization of Various Formulation and Processing Parameters for the Development of Aquasomes - Katharotiya, Khushboo; Katharotiya, Dhaval; Jha, Lalit Lata (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: The research aims to enhance understanding of aquasome preparation, offering insights into optimizing formulations for potential applications in drug delivery systems. Materials and Methods: Aquasomes composed of lactose and trehalose as oligosaccharides encapsulate calcium phosphate cores. The cores synthesized by sonication and co-precipitation methods were screened based on % yield for calcium phosphate synthesis. Various coating methods were employed for the screening based on carbohydrate loading capacity. The study evaluates these formulations to optimize carbohydrate loading and particle size for potential applications in bioactive drug delivery to enhance drug loading capacity and minimize use of bioactive drugs for initial screening and optimization. Results and Discussion: Ceramic core preparation via sonication yielded higher percentages (69.6%) compared to co-precipitation (54.06%). Trehalose demonstrated superior carbohydrate loading (67.74%) compared to lactose (55.81%) using the lyophilisation method. The Plackett-Burman design identified four significant factors affecting particle size, which are sonication time, amplitude, temperature and carbohydrate concentration. The Central Composite Design (CCD) optimization revealed that increased sonication time and carbohydrate amount led to higher carbohydrate loading. Lower sonication temperatures resulted in greater carbohydrate loading. Particle size decreased with increased sonication time but increased with higher carbohydrate amounts and sonication temperatures. The optimized formulation achieved a carbohydrate loading of 104.17±0.021 mg and a particle size of 407.2±0.34 nm, closely matching predicted values. Conclusion: The study shows sonication time, temperature and carbohydrate concentration influence aquasome development. Essential for optimizing their performance in various biomedical applications, particularly in drug delivery. Further exploration and validation of these optimized formulations in practical settings are warranted to fully exploit their potential benefits.
Keywords: Aquasomes; Calcium Phosphate; Carbohydrate; Sonication; Plackett-Burman design